2006
DOI: 10.1055/s-2006-939769
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation in Hemolytic Uremic Syndrome

Abstract: Platelet consumption in platelet-fibrin aggregates leading to thrombocytopenia and small vessel obstruction are major features of the hemolytic uremic syndrome (HUS). Although thrombocytopenia has been correlated to poor prognosis, the mechanisms by which thrombocytopenia develops in HUS have not been completely elucidated. However, plausible explanations have been platelet contact with thrombogenic surfaces and/or direct contact with an aggregating agent. This article summarizes several mechanisms of platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 145 publications
(171 reference statements)
0
43
0
2
Order By: Relevance
“…Hemoglobinemia, disordered platelet function, and thrombosis are features of paroxysmal nocturnal hemoglobinuria, thrombotic thrombocytopenic purpura, hemolytic-uremic syndrome, and disseminated intravascular coagulation. There is evidence of platelet activation in these conditions, [52][53][54][55][56][57][58][59] but the potential contribution of NO scavenging by plasma hemoglobin to platelet activation and thrombosis has not yet been investigated. This mechanism is supported by evidence of NO scavenging by cell-free cross-linked hemoglobin artificial blood substitutes in rats, promoting platelet deposition at sites of subintimal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobinemia, disordered platelet function, and thrombosis are features of paroxysmal nocturnal hemoglobinuria, thrombotic thrombocytopenic purpura, hemolytic-uremic syndrome, and disseminated intravascular coagulation. There is evidence of platelet activation in these conditions, [52][53][54][55][56][57][58][59] but the potential contribution of NO scavenging by plasma hemoglobin to platelet activation and thrombosis has not yet been investigated. This mechanism is supported by evidence of NO scavenging by cell-free cross-linked hemoglobin artificial blood substitutes in rats, promoting platelet deposition at sites of subintimal injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its function in complement regulation, FH can act as an adhesion ligand for neutrophils and platelets and may also participate in immune adherence of various host tissues (1,13,20). Therefore, we used human cell lines, including those from both the upper and lower respiratory tracts, to investigate FH-mediated pneumococcal adherence to tissues in which PspC expression is important for infection (2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its function in complement regulation, FH can act as an adhesion ligand for neutrophils and platelets and may also participate in immune adherence of various host tissues (1,13,20). In this study, we have investigated whether FH mediates adherence of pneumococci to human umbilical vein endothelial cells (HUVEC).…”
mentioning
confidence: 99%
“…of endothelium, 18 red cells, 19 and platelets. 20 Clinically, STEC-HUS can be nearly as severe as aHUS (with mortality of up to 5%), as exemplified during the wide outbreak in Germany and some other European countries in 2011. 21 The main reason why gastrointestinal infection particularly affects kidneys is thought to be the tissue tropism of Shiga-toxin on the basis of the strong expression of Gb3 on the glomerular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…40 Although platelets are normally protected from complement attack by the concerted action of factor H and membrane regulators, 94 this protection is impaired in aHUS. 20 We have recently shown that protection of platelets from complement attack by factor H requires sialic acids on the cell membrane in vitro. 59 Therefore, impaired alternative pathway regulation is a logical explanation for thrombocytopenia and could also contribute to formation of platelet-rich microvascular thrombi.…”
mentioning
confidence: 99%